ANALISIS KERJA WANITA PETANI PADI DI KECAMATAN PIDIE KABUPATEN PIDIE - Raihani, Raihani (Jurnal Mentari, 2011)
This study aims to determine the activities will be undertaken by a woman who worked as rice farmers in the district of Pidie and determine the pattern of working hours of women working as rice farmers in the district of Pidie. The study population was female rice farmers in the district of Pidie. Given the population that much, then researchers took the women rice farmers in the district of Pidie as many as 40 people sampled in this study. The data was collected by spreading questionnaire and observation and data processing method using a percentage formula. Based on the results of research that has been done can be concluded that the type of work outside the hours of farming respondents were household activities (reproduction), looking for additional income, basic activities and social events. The pattern of working hours to activities highest respondent base is 8 hours, both household activities that is 5.5 hours, all three activities seek additional revenue that is 3 hours and for social activities is 0.5 hours. Key words: working hours, women rice farmersDAFTAR PUSTAKA Arintadinata, S. 1982. Peningkatan Partisipasi Masyarakat dalam Pembangunan Pertanian. Jakarta: BLPP. Arikunto, Suharsimi.  2002. Prosedur Penelitian Suatu Pendekatan Praktek. Jakarta: Rineka Cipta. Arivia, Gadis. 1999. “Politik Susu”. Pemberontakan Ruang Publik, dalam Suara Perduli 1999. Catatan Perjalanan Suara Ibu Perduli. Jakarta: Yayasan Jurnal Perempuan. Astiti, Ni Wayan Sri. Tanpa Tahun. Partisipasi Perempuan Dalam Pengelolaan System Irigasi Subak di Bali. Skripsi. (http://e.journal.unud.ac.id/abstrak/partisipasi%20subak,%20subak%20 psw.pdf, diakses 20 Oktober 2010) Kasimin, dkk. 1998. Analisis Curahan Jam Kerja Wanita Dalam Rumah Tangga dan Masyarakat (Studi Kasus Kotamadya Banda Aceh dan Kabupaten Aceh Besar). Banda Aceh: Laporan Penelitian. Ihromi, TO. 1980. Kajian Wanita dalam Pembangunan. Jakarta: Penerbit Yayasan Obor Indonesia. Sajogyo, Pudjiwati. 1983. Peranan Wanita dalam Perkembangan Masyarakat Desa. Jakarta: YIIS. Simanjuntak, Tuti.2007. Analisis Curahan Tenaga Kerja dan Pendapatan Petani Dafep pada Usaha Tani Padi Sawah. Skripsi. (http://repository.usu.ac.id. Diakses 2 Oktober 2010) Riningsih. 2005. Pengaruh Modal Kerja dan Satuan Jam Kerja terhadap Pendapatan pada Industry Kecil Pengrajin Genting di Desa Karang Asem Kecamatan Wirosari Kabupaten Grobogan. Skripsi. (http://digilib.unnes.ac.id. Diakses 3 oktober 2010).